Pedagogies of Disaster - Matthew Charles; Jonida Gashi; Judith Balso; Nick Skiadopoulos; Sina Badiei; Denisa Kera; Tijana Stevanović; Justin Joque; Vincent W. J. van Gerven Oei (ed. and author); Adam Staley Groves (ed. and author); Nico Jenkins (ed. and author); Christopher Fynsk; et al. (Book collections on Project MUSE., 2013)
We live in an era where the university system is undergoing great changes owing to developments in financing policies and research priorities, as well as changes in the society in which this system is embedded. This change toward a more market-oriented university, which also has immediate effects in academic peripheries such as the Balkans, the Middle East, or South-East Asia, is of great influence for the pedagogical practice of "less profitable" academic areas such as the Humanities: philosophy, languages, sociology, anthropology, history. Because of the absence of a historically grounded establishment of the Humanities, academic peripheries, usually accompanied by a weak civil society infrastructure, seem to offer the most fertile ground for rethinking the Humanities, their pedagogical practice, and their politics, as well as the greatest threats, such as the ongoing capitalization of research, and profitability as the norm of educational achievement. The sprawling presence of for-profit universities and in academic peripheries such as Albania and Kosovo is indicative of this problematic, as are consistent underfunding of universities and the relentless budget cuts in American and English, and to a lesser extent European, universities. Motivations for this ongoing attack on the university are often driven by a political system or a politics with an aggressive stance to critical thought.